Hubungan Antara Konsumsi Rokok Dengan Status Nutrisi Pada Remaja - Bagaskoro, Anan; Amelia, Vivi Leona (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to find out the correlation between cigarette consumption and teenage students' nutrition. Method: This was an observational research with descriptive-analytical design. The samples of this research were the seventh and eighth graders that were taken using proportional sampling. The data were analyzed using Spearman rank. Results: The results showed that 22.9% of the students were at the age of 15 years old and did not smoke, 33 students (39.8%) were female and did not smoke. The most dominant cigarette consumption on teenage students was on the 33 respondents (39.8%) who did not smoke, and the most dominant nutrition status on teenage students were 54 respondents (65.1%). Conclusion: There was a correlation between cigarette consumption and teenage students' nutrition